DENTURE BASE POLYMERS EVOLUTION AND IMPROVEMENTS-A LITERATURE REVIEW - Dana Gabriela Budală; Elena Raluca Baciu; Dan Nicolae Bosînceanu; Zinovia Surlari; Carina Balcoș; Maria Bolat; Oana Țănculescu (Romanian Dental Association for Education, 2020)
The improvement of the basic properties of dental restorative materials, such as their mechanical, physical, aesthetic, and bonding properties, has been dramatic and the current materials on the market show excellent clinical performance. This review article compiles the characteristics of resin based dentures materials and the efforts made in order to improve the main features and to point out future perspectives.